In-depth population genetic study of Vitis vinifera ssp. sylvestris from the Black Sea region and its virome - Belkina, Daria; Stepanov, Ilya; Makarkina, Marina; Porotikova, Elena; Lifanov, Ilya; Kozhevnikov, Evgeniy; Gorislavets, Svetlana; Vinogradova, Svetlana (Frontiers in Plant Science, 2025)
The spread of cultivated grapevine from primary centers of origin is inevitably accompanied by the range expansion of its pathogens, including viruses. A limited number of wild Vitis vinifera L. ssp. sylvestris (Gmelin) Hegi populations have survived in the centers of grapevine domestication and can be used for comprehensive studies. We analyzed 50 grapevines collected in protected areas of the Black Sea region, which belong to the Caucasian domestication center. Based on genotyping of grapevines using simple sequence repeats as DNA markers, we determined the phylogenetic placement of V. vinifera ssp. sylvestris from the Black Sea region compared to cultivated and wild grapevines of the world. Using high-throughput sequencing of total RNA, we obtained the viromes of these grapevines. Ten viruses and one viroid were identified. The most common viruses detected were Vitis cryptic virus, grapevine rupestris stem pitting–associated virus, grapevine Pinot gris virus, and grapevine virus T. Among the economically significant viruses, we identified grapevine leafroll-associated virus 1 and grapevine virus A. A total of 91 complete or nearly complete virus genomes and one viroid genome were assembled, and phylogenetic analysis was performed. Two novel (+) ssRNA viruses were discovered, tentatively named Abrau grapevine-associated virus in the order Hepelivirales and Taurida grapevine-associated virus in the order Picornavirales. It is important to comprehensively consider the phylogeography of both viruses and their plant hosts. This is the first study that simultaneously addresses the population genetics of V. vinifera ssp. sylvestris from the Caucasian domestication center and its viruses.